2018
DOI: 10.1002/mp.13082
|View full text |Cite
|
Sign up to set email alerts
|

Classification of breast lesions in ultrasonography using sparse logistic regression and morphology‐based texture features

Abstract: Using ARD, the proposed CAD system selects five new features for breast tumor classification and outperforms state-of-the-art, making a reliable and complementary tool to help clinicians diagnose breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…The resulting classification attained an accuracy of 91.11%. (Nemat et al, 2018) proposed the utilization of a computer-aided diagnostic system (CAD) that incorporates a preprocessing operation to improve the quality of ultrasound depicting breast cancers. Subsequently, the use of the watershed method was employed for the purpose of segmenting the breast tumor.…”
Section: Classical Methodsmentioning
confidence: 99%
“…The resulting classification attained an accuracy of 91.11%. (Nemat et al, 2018) proposed the utilization of a computer-aided diagnostic system (CAD) that incorporates a preprocessing operation to improve the quality of ultrasound depicting breast cancers. Subsequently, the use of the watershed method was employed for the purpose of segmenting the breast tumor.…”
Section: Classical Methodsmentioning
confidence: 99%
“…The shape-based features very effectively differentiated various breast lesions in some researches [18,19] and showed that these features are more appropriate for breast tumor detection. The objective of shape-based features is to measure contour and shape characteristics of breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In CADx systems, the main focus is the automatic finding and classification of breast lesion. Imaging modalities supporting the type of texture features [14][15][16] and shape-based features [18][19][20] have been employed to identify breast cancer ailment. However, it is still a difficult job to choose appropriate features for finding cancer at its early stage [19].…”
Section: Introductionmentioning
confidence: 99%
“…Results for classification of the 57 extracted texture and shape features giving the highest classification accuracy of 84.6%. Another literature [5] proposed a watershed method for semi-automatic tumor segmentation. After extracting a set of 855 features including shape or texture from each tumor area, a Bayesian Automatic Relevance Detection (ARD) was used to reduce the feature and dimensionality.…”
Section: Introductionmentioning
confidence: 99%